Chinese Herbal Medicine for Psoriasis: Evidence From 11 High-Quality Randomized Controlled Trials - Luo, Yue; Chen, Jiale; Kuai, Le; Zhang, Ying; Ding, Xiaojie; Luo, Ying; Ru, Yi; Xing, Meng; Li, Hongjin; Sun, Xiaoying; Li, Bin; Li, Xin (Frontiers in Pharmacology, 2021)
Background: Chinese herbal medicine (CHM) provides a theoretical basis for the treatment of psoriasis with considerable benefits and a low toxicity. The purpose of this quantitative study was to show high-quality evidence of the efficacy and safety of CHM for the treatment of psoriasis to promote its clinical application. Methods: Several databases were systematically searched including PubMed, Embase, Cochrane Central Register of Controlled Trials, China Network Knowledge Infrastructure, Chinese Scientific Journals Database, and Wan Fang Database. High-quality randomized controlled trials that compared CHM with non-CHM interventions were included. The RevMan5.3 software was used to calculate risk ratios (RR) at 95% confidence intervals (CI) and conduct the meta-analysis. Results: Altogether, 1,215 patients participated in this study, including 711 in the experimental group and 504 in the control group. The psoriasis area severity index (PASI) score of the CHM group was significantly lower than that of the placebo group (MD, −4.02; 95% CI, −6.71 to −1.34; p = 0.003). To achieve PASI-60 and PASI-75, the arrival rate of the CHM group was higher than that of the placebo group (PASI-60: RR, 3.52; 95% CI, 1.17 to 10.61; p = 0.03; PASI-75: RR, 9.87; 95% CI, 3.11 to 31.31; p = 0.0001). Furthermore, the efficacy rate was higher in patients receiving CHM than in those receiving placebo (RR, 1.72; 95% CI, 1.01 to 2.93; p = 0.04). The results suggested a greater impact of CHM in improving the dermatology life quality index (DLQI) of patients (MD, −2.12; 95% CI, −3.75 to −0.49; p = 0.01). Regarding pruritus severity, there was no significant difference between the two groups (MD, −1.90; 95% CI, −3.79 to −0.01; p = 0.05). The meta-analysis revealed that the recurrence rate (RR, 0.74; 95% CI, 0.32 to 1.71; p = 0.48) and proportion of adverse events (RR, 1.36; 95% CI, 0.95 to 1.93; p = 0.09) associated with using CHM were similar to those associated with using a placebo. Conclusion: CHM appears safe and effective in the treatment of psoriasis and has a great positive impact on the DQLI of patients; however, CHM could not completely eliminate skin lesions, improve pruritus severity, and reduce the recurrence rate.